Winnipeg West : Painting and Sculpture in Western Canada : 1945-1970 - Varley, Christopher; The Edmonton Art Gallery, Edmonton; Surrey ARt Gallery, Surrey; Rodman Hall Arts Centre, St. Catharines; Sarnia Public Library and Art Gallery, Sarnia (Edmonton : Edmonton Art Gallery, 1983)
Binning, B.C. ; Harris, Lawren ; Shadbolt, Jack ; Jarvis, Donald ; Smith, Gordon ; Plaskett, Joseph ; Hughes, E.J. ; etc.
Winnipeg West : Painting and Sculpture in Western Canada : 1945-1970, The Edmonton Art Gallery, Edmonton, September 2 - October 10, 1983 / Surrey ARt Gallery, Surrey, October 20 - November 13, 1983 / Rodman Hall Arts Centre, St. Catharines, December 2, 1983 - January 1, 1984 / Sarnia Public Library and Art Gallery, Sarnia, January 13 - February 5, 1984 / etc.
boek